Development of High Voltage Pulse Power Supply For Dielectric Barrier Discharge (DBD) Plasma - MOHAMAD ROSDI, SITI NORHAMISAH; Sahari, Norain (Progress in Engineering Application and Technology, 2021)
In conventional DBD plasma, an AC power supply with a 50 Hz frequency is used to generate a high voltage in the DBD plasma reactor. However, the stable DBD plasma at air atmospheric pressure is difficult to achieve in low frequency power supply. Apart from that, a versatile power supply that can meet the various demand is essential. To generate plasma in DBD reactor, it is necessary to have a high frequency power supply. In this study, a portable and adjustable high voltage pulse power supply for DBD plasma generation is presented. The input driver circuit is designed by using two 555 timers to chop the electricity into pulse and then connected it to the ignition coil to step up the 12 DC voltage into 10 kV high voltage. The value of the capacitor and resistor was varied to study the effect on the output frequency of the pulse circuit by using Proteus simulation. The result shows that the simulation process has proven with the calculation to be right and yields the desired outcome based on the designed values. Then, the output of the high voltage pulse generator was compared with the simulation and hardware implementation. This high voltage pulse generator achieves its objective that can be used to generate DBD plasma at atmospheric pressure in the future study. Besides, it can replace the conventional pulse generator which used low frequency to generate high voltage.